Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan terhadap Profitabilitas (Studi Kasus pada Perusahaan Sektor Pertambangan Mineral dan Batubara Periode Tahun 2019-2021) - Rohmah, Euis Siti; Manullang, Asna (STIE PENA, 2024)
Profitability ratios are influenced by various financial factors which can be measured using financial ratios. The aim of this research is to analyze the effect of cash turnover, accounts receivable turnover, and turnover inventory on profitability in mineral and mining companies coal listed on the Indonesia Stock Exchange for the 2019-2021 period. The population of this research is mineral and mining companies coal listed on the Indonesia Stock Exchange for the 2019-2021 period. Method The sampling used was purposive sampling and 19 were obtained companies as samples. The method used is the regression analysis method multiple linear The results of this research are based on the t test results, cash turnover is not has a significant influence on profitability. While rotation receivables have a positive and significant influence on profitability. Rotation inventory does not have a significant effect on profitability. Research result along with the F test shows that all variables are independent significant effect on profitability. The value of the coefficient of determination (r2) Which adjusted by 0.235 indicates that a profitability of 23.5% can be achieved explained by the independent variables cash turnover, receivables turnover and inventory turnover. Meanwhile, the remaining 76.5% is explained by other variables.